Perceived muscular tension, job strain, physical exposure, and associations with neck pain among VDU users; a prospective cohort study. Issue 6 (18th May 2004) - Wahlström, J; Hagberg, M; Toomingas, A; Wigaeus Tornqvist, E
Abstract : Aims: To determine whether perceived muscular tension, job strain, or physical exposure are associated with increased risk of developing neck pain among VDU users. Methods: A baseline questionnaire was answered by 1283 respondents, of whom 671 were free from neck pain at baseline. Perceived muscular tension, job strain, and physical exposure were assessed at baseline. Information about newly developed neck pain was collected in 10 follow up questionnaires and the case definition was the first report of such pain in any of the follow up questionnaires. Median follow up time was 10.9 months. Results: Both men and women who perceived muscular tension at least a few times per week, compared to those who had not perceived muscular tension the preceding month, had an incidence rate ratio (IRR) of 1.9 (95% CI 1.25 to 2.93) for developing neck pain, when stratifying for sex. High perceived muscular tension was associated with an increased risk (IRR 1.6, 95% CI 1.02 to 1.91), even when controlling for job strain, physical exposure, and age in the model stratified by sex. Conclusions: Perceived muscular tension was associated with an increased risk of developing neck pain among VDU users. The combination of high job strain and high perceived muscular tension was associated with higher risk of developing neck pain than the combination of high physical exposure and high perceived muscular tension. There was an indication of an excess risk due to interaction between high physical exposure and high job strain.